Endocan Is an Independent Predictor of Heart Failure-Related Mortality and Hospitalizations in Patients with Chronic Stable Heart Failure. (4th April 2019) - Kosir, Gorazd; Jug, Borut; Novakovic, Marko; Mijovski, Mojca Bozic; Ksela, Jus
Abstract : Background . Heart failure (HF) is characterized by unfavorable prognosis. Disease trajectory of HF, however, may vary, and risk assessment of patients remains elusive. In our study, we sought to determine the prognostic impact of endocan—a novel biomarker of endothelial dysfunction and low-grade inflammation—in patients with heart failure. Methods . In outpatients with chronic HF, baseline values of endocan were determined and clinical follow-up for a minimum of 18 months obtained. A multivariate Cox proportional hazard model was built for HF-related death or hospitalization requiring inotropic support. Results . A total of 120 patients (mean age 71 years, 64% male, mean LVEF 36%) were included. During a mean follow-up of656 ± 109 days, 50 patients (41.6%) experienced an event. On Cox multivariate analysis, endocan values emerged as an independent predictor of HF prognosis (HR, 1.471 CI 95% 1.183-1.829, p = 0.001, for each 1 ng/mL increase) even after adjustment for age, gender, HF etiology, LVEF, NYHA class, NT-proBNP, and exercise tolerance. Conclusions . Endocan is an independent predictor of HF-related events in chronic HF individuals and represents a promising tool for risk assessment of HF patients.